Much More Than IL-17A: Cytokines of the IL-17 Family Between Microbiota and Cancer - Brevi, Arianna; Cogrossi, Laura Lucia; Grazia, Giulia; Masciovecchio, Desirée; Impellizzieri, Daniela; Lacanfora, Lucrezia; Grioni, Matteo; Bellone, Matteo (Frontiers in Immunology, 2020)
The interleukin-(IL-)17 family of cytokines is composed of six members named IL-17A, IL-17B, IL-17C, IL-17D, IL-17E and IL-17F. IL-17A is the prototype of this family, and it was the first to be discovered and targeted in the clinic. IL-17A is essential for modulating the interplay between commensal microbes and epithelial cells at our borders (i.e., skin and mucosae), and yet, for protecting us from microbial invaders, thus preserving mucosal and skin integrity. Interactions between the microbiota and cells producing IL-17A have also been implicated in the pathogenesis of immune mediated inflammatory diseases and cancer. While interactions between microbiota and IL-17B-to-F have only partially been investigated, they are by no means less relevant. The cellular source of IL-17B-to-F, their main targets and their function in homeostasis and disease distinguish IL-17B-to-F from IL-17A. Here, we intentionally overlook IL-17A, and we focus instead on the role of the other cytokines of the IL-17 family in the interplay between microbiota and epithelial cells that may contribute to cancer pathogenesis and immune surveillance. We also underscore differences and similarities between IL-17A and IL-17B-to-F in the microbiota-immunity-cancer axis, and we highlight therapeutic strategies that directly or indirectly target IL-17 cytokines in diseases.